Inactivated vaccine against Aujeszky's disease - Zhanat B. Kondibaeva (Veterinary World, 2021)
Background and Aim: The Aujeszky's disease, also known as Pseudorabies, remains one of the most problematic fulminant diseases in domestic animals, affecting the central nervous system. The study aimed to investigate the effect of an inactivated vaccine against Aujeszky's disease based on "Kordai" virus strain.